Template for Assessing the Governance of Public Water Supply and Sanitation Service Providers : A Tool for Understanding Water System Effectiveness - Locussol, Alain; Ginneken, Meike van (World Bank, Washington, DC, 2012)
The template is a tool to assess the performance of an urban water supply and sanitation (WSS) service provide by taking into account the governance, policy, and management context it operates in. The template complements extensive work done on comprehensive performance indicators through the International Benchmarking Network for Water and Sanitation Utilities (IB-NET). These metric indicators measure service coverage, efficiency, reliability, financial sustainability, environmental sustainability, and affordability to provide reliable data about the quality of WSS service and the performance of WSS service providers.